2023
DOI: 10.3390/app132413150
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antibacterial Studies of New Cu(II) and Pd(II) Complexes with 6-Methyl-2-Thiouracil and 6-Propyl-2-Thiouracil

Petya Marinova,
Mariyan Hristov,
Slava Tsoneva
et al.

Abstract: The aim of the present study is to synthesize new metal complexes of 6-methyl-2-thiouracil and 6-propyl-2-thiouracil, elucidate their structures, and investigate their biological properties. All metal complexes were obtained after mixing water solutions of the corresponding metal salts and the ligand dissolved in DMSO and water solutions of NaOH in a metal-to-ligand ratio of 1:4:2. The structures of the new compounds are discussed based on melting point analysis (MP-AES) for Cu and Pd, UV-Vis, IR, ATR, 1H NMR,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 42 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…The highest antimicrobial activity was exhibited by the Cu(II) complex with 6-methyl-2thiouracil [27]. It was active against all of the test microorganisms.…”
Section: Biological Activities Antibacterial Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…The highest antimicrobial activity was exhibited by the Cu(II) complex with 6-methyl-2thiouracil [27]. It was active against all of the test microorganisms.…”
Section: Biological Activities Antibacterial Activitymentioning
confidence: 99%
“…New complexes of Cu(II) and Pd(II) with 6-methyl-2-thiouracil and 6-propyl-2-thiouracil have been obtained [27]. All metal complexes have been obtained after mixing water solutions of the corresponding metal salts and the ligand dissolved in DMSO and water solutions of NaOH, in metalto-ligand ratio 1:4:2.…”
Section: Synthesis Of Metal Complexes With 2-thiouracil and Its Deriv...mentioning
confidence: 99%
See 2 more Smart Citations
“…The compound structure has been reviewed based on melting point analysis, MP-AES for Cu and Pd, UV-Vis, IR, ATR, 1 H NMR, 13 C NMR, and Raman spectroscopy. The interpretation of complex spectra is assisted by the data for 6-methyl-2-thiouracil and 6-propyl-2-thiouracil obtained from 1 H-1 H COSY, DEPT-135, HMBC, and HMQC spectra [32]. We have suggested that in the Cu(II)L1 complex, the ligand could probably coordinate in a monodentate way through S2 and/or O4 atoms.…”
Section: Synthesis Of Metal Complexes With 2-thiouracil and Its Deriv...mentioning
confidence: 99%